2009
DOI: 10.1007/s10729-009-9119-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of comorbidity on breast cancer patient outcomes

Abstract: The objective of this paper is to model the impact of comorbidity on breast cancer patient outcomes (e.g., length of stay and disposition). Previous studies suggest that comorbidities may significantly affect mortality risks for breast cancer patients. The 2006 AHRQ Nationwide Inpatient Sample (NIS) is used to analyze the relationships among comorbidities (e.g., hypertension, diabetes, obesity, and mental disorder), total charges, length of stay, and patient disposition as a function of age and race. A multifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Furthermore, previous studies have shown that hospitalized breast cancer patients present with slightly different characteristics compared with the general inpatient population, and may have different patterns of admission such as shorter lengths of stay, fewer diagnoses, more procedures on average, and significantly lower total hospital charges [30]. This raises the possibility that breast cancer patients are being admitted for specific, targeted purposes, such as surgery, and therefore minor complications may be underreported, potentially resulting in an underestimation of the associations observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that hospitalized breast cancer patients present with slightly different characteristics compared with the general inpatient population, and may have different patterns of admission such as shorter lengths of stay, fewer diagnoses, more procedures on average, and significantly lower total hospital charges [30]. This raises the possibility that breast cancer patients are being admitted for specific, targeted purposes, such as surgery, and therefore minor complications may be underreported, potentially resulting in an underestimation of the associations observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However the HCUP-NIS does not include information on patient outcomes after discharge, therefore complications and mortality occurring after hospital discharge were not included in our analysis. In addition, since the dataset includes only de-identified patient records, it was not possible to exclude duplicate records if the same patient was admitted multiple times in the same year [30].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Studying the impact of comorbidities provides information regarding disease management, cost structure and resource utilization. Chronic diseases (CDC, 2009b) in particular, though controllable, account for billions in healthcare costs annually (CDC, 2009c;Zhang et al, 2010). In this study, hypertension, diabetes, mental disorders and obesity are selected as comorbid conditions of interest with respect to HIV, with a particular focus on mental disorders as they have been recognized to have a special relationship with HIV in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using large hospitalization data (Zhang et al, 2010;Elixhauser et al, 1998) have resulted in small R 2 values when using least squares regression with the CoxBox transformation (Box and Cox, 1964). Since these data have a large number of variables, the proportion of variance explained by the fit is usually low when only a subset of the covariates are added to the regression models.…”
Section: Introductionmentioning
confidence: 99%
“…Many older patients will not only tolerate aggressive therapy, but they will thrive as a productive subset of society, making valuable contributions as elder statesmen, senior professionals and academicians, mentors, and grandparents or great-grandparents. Can we replace or supplement age as ''just a number'' with a descriptor of medical status as a function of comorbidities, as suggested by Zhang et al 1 Two manuscripts from this issue of Annals of Surgical Oncology support the importance of looking beyond age as number that might dogmatically preclude curative-intent surgery for either a common malignancy such as breast cancer or a less common tumor such as esophageal cancer. Laki et al compared outcomes following breast cancer surgery for patients C80 years, 75-80 years, and 70-75 years, finding results that were similar between these age categories and comparable to those reported in the medical literature for younger patients.…”
mentioning
confidence: 99%